2008
DOI: 10.1186/1477-9560-6-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining warfarin underutilization rates in patients with atrial fibrillation: Detailed chart review essential to capture contraindications to warfarin therapy

Abstract: Introduction: Atrial fibrillation affects an estimated 2.5 million Americans and incurs an average annual stroke risk of 4.5% per year. Despite warfarin reducing stroke risk by approximately 66%, prior studies show warfarin usage rates to be about 50%. However, the methods that define warfarin as "inappropriate underutilization" might not be sensitive enough to pick up relative contraindications. We assessed the inappropriate underutilization of warfarin in atrial fibrillation patients at our hospital by abstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 31 publications
(30 reference statements)
1
41
0
Order By: Relevance
“…In a recent study of atrial fibrillation treatment at a large, urban medical center, 17 approximately 55% of patients received warfarin. Detailed review of the medical records revealed actual or perceived contraindications to warfarin in most of the remainder, leaving only approximately 7% without a documented reason for not prescribing warfarin.…”
Section: Contraindications To Warfarinmentioning
confidence: 99%
“…In a recent study of atrial fibrillation treatment at a large, urban medical center, 17 approximately 55% of patients received warfarin. Detailed review of the medical records revealed actual or perceived contraindications to warfarin in most of the remainder, leaving only approximately 7% without a documented reason for not prescribing warfarin.…”
Section: Contraindications To Warfarinmentioning
confidence: 99%
“…Sadly, the suboptimal proportion of anticoagulated patients in our study population is not that different from various other reports from real-world practice. [2][3][4][5] We agree with Gasparovic and Kopjar's comment that rhythm therapy cannot be equated with sinus rhythm. Unfortunately, we did not have ECG information to determine sinus rhythm in patients.…”
mentioning
confidence: 33%
“…One of nine patients had treatment with OAC drugs withheld due to an increased risk of bleeding, compared with as many as one-third reported by other researchers. 4 Other important factors for restraining treatment with OAC drugs in this study were declined general condition (14%) and a history of repeated falls (7%). The importance of these three reasons increased with higher risk scoring and age.…”
Section: Discussionmentioning
confidence: 98%